2019 IEEE 10th International Conference on Biometrics Theory, Applications and Systems (BTAS) 2019
DOI: 10.1109/btas46853.2019.9185997
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Algorithm Enabled Similarity-Based Attack on Cancellable Biometrics

Abstract: Cancellable biometrics (CB) as a means for biometric template protection approach refers to an irreversible yet similarity preserving transformation on the original template. With similarity preserving property, the matching between template and query instance can be performed in the transform domain without jeopardizing accuracy performance. Unfortunately, this trait invites a class of attack, namely similarity-based attack (SA). SA produces a preimage, an inverse of transformed template, which can be exploit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…If an attacker can access the protected template, he/she can apply a search algorithm to generate first guesses randomly, transform them to the protected domain, compute the distances with the protected template, use the information to improve the probability of success with new guesses, and repeat the process until reaching a successful guess. The work in [15] confirms the vulnerability of BioHashing and Bloom-filter schemes to a Genetic Algorithm enabled similarity-based attack. The work in [14] introduces non-linearity in the transformation with the aid of a deep neural network, but this requires retraining whenever a new user is enrolled.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…If an attacker can access the protected template, he/she can apply a search algorithm to generate first guesses randomly, transform them to the protected domain, compute the distances with the protected template, use the information to improve the probability of success with new guesses, and repeat the process until reaching a successful guess. The work in [15] confirms the vulnerability of BioHashing and Bloom-filter schemes to a Genetic Algorithm enabled similarity-based attack. The work in [14] introduces non-linearity in the transformation with the aid of a deep neural network, but this requires retraining whenever a new user is enrolled.…”
Section: Introductionmentioning
confidence: 54%
“…In the other side, most of cancelable biometric schemes apply similarity-preserving transformations, also called Locality Sensitive Hashing, in order to preserve in the protected domain the accuracy performance obtained in the unprotected domain [14] [15]. The problem is that this similarity or distance-preserving property (distances between unprotected samples are nearly the same as the distances between protected samples) can be exploited by similaritybased attacks that break these schemes.…”
Section: Introductionmentioning
confidence: 99%
“…They also demonstrated that the irreversibility of both schemes is overestimated. Moreover, Wang et al [25] proposed a constrained optimization similarity-based attack (CSA) based on a genetic algorithm enabled similarity-based attack originally proposed in [26] and demonstrated its effectiveness in breaching IoM This work is licensed under a Creative Commons Attribution 4.0 License. For more information, see https://creativecommons.org/licenses/by/4.0/ This article has been accepted for publication in a future issue of this journal, but has not been fully edited.…”
Section: Authenticationmentioning
confidence: 99%
“…For instance, the authors of some CB schemes demonstrate the security properties of their methods under specific transformation parameter settings and show the commitment of their methods to the recognition accuracy preservation under different parameter settings. Several recent studies [15]- [26] showed that the security of many CB schemes against invertibility and linkability attacks are overestimated or cannot be assured without significant de-terioration in recognition accuracy. Therefore, analyzing the security properties of recent CB schemes is of paramount importance in order to assess the suitability of adopting such schemes in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by these characteristics, many biometric protection scheme algorithms have been proposed in the field of cancellable biometric recognition [25]- [27]. However, the security problems must be considered and the bloom filter-based has been cracked as reported in [28]. During design the biometric protection scheme, biometric feature type is one vital factor, such as binary code, real number vector.…”
Section: Related Workmentioning
confidence: 99%